Humor and Co-Creation as Levers of Valorization of Tourism Attractions: Case Study from Vodnjan, Croatia (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
Tourists are highly selective, they are looking for the unforgettable experiences and they want to familiarize with the tradition and the culture of the local residents, which represents a great challenge for the tourism products and service providers because they constantly have to create new and interesting activities, because tourists are no longer interested in sightseeing of the cultural and the historical heritage, but they also want to be a part of it. The purpose of this case study is to affect the perceptions of visitor of Vodnjan (Croatia) by enriching their cultural experience. The goal is to propose a model of collaboration of tourists in the creation of such experiences. The appeal to humor, as a still under researched topic in function of tourism, as well as the principles of co-creation, rarely used in tourism, were combined to help revalorize Vodnjan's tourism attractions and the destination itself.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.